Domestic demand-based economic globalization and inclusive growth - Jianghuai Zheng; Chunmiao Shen (China Political Economy (CPE), 2019)
Purpose The purpose of this paper is to propose policy recommendations that resort to the domestic market to achieve inclusive growth from an open perspective. Design/methodology/approach How will economic globalization based on domestic demand affect economic growth and income distribution in an open and large country? With the aim of discussing the mechanism of the impact of expanding domestic demand on the inclusive growth from an open perspective, this paper incorporates the Global Value Chains vs National Value Chains (GVC-NVC) competition, which is triggered by foreign investments attracted by the domestic demand scale into an endogenous growth model with "Schumpeterian Innovation." Findings Theoretical analysis indicates the following findings: although domestic demand-based economic globalization can promote transnational inclusive growth across countries, it is not conducive to national (domestic) inclusive growth; the impacting effect of domestic demand scale on inclusive growth across countries is subject to the moderating effect of the development maturity of the labor market; and the impacting effect of domestic demand scale on national inclusive growth is subject to the joint moderating effect of the development maturity of the labor market and labor skill structure. Originality/value First, this paper examines the impact of domestic demand-based economic globalization on the inclusiveness of economic growth from an open perspective, which deepens the existing theory of intra-product specialization and inclusive growth. Second, the paper puts the sequential production process into Schumpeterian growth model and reveals the mechanism that domestic demand affects inclusive growth. Third, the study finds that the enhancement of labor market efficiency, transfer payments to low-skilled labor and the creation of a fair competitive market environment will contribute to the globalization of a domestic demand-oriented economy, which provides a policy-making basis for government sectors.
Keywords: 330; Domestic demand; Economic globalization; Inclusive growth